First description of Mycobacterium tuberculosis Beijing genotype in Argentina Primera descripción del genotipo Beijing de Mycobacterium tuberculosis en la Argentina - N. Morcillo; B. Di Giulio; C. Chirico; A. Kuriger; A. Dolmann; A. Alito; M. Zumárraga; D. Van Soolingen; K. Kremer; A. Cataldi (Revista Argentina de Microbiología, 2005)
During a population-based study to genotype isolates of Mycobacterium tuberculosis from Buenos Aires Northern suburbs, we found isolates with molecular patterns related to those of the Beijing genotype. Five out of 590 (0.85%) patients had isolates with spoligopattern identical to that of the Beijing family. Since two of these isolates showed identical IS6110RFLP pattern, we found only four different patterns containing 11 to 19 bands. The isolates were obtained from young people (including a 7 years-old child) who were born in Argentina, and were living in a small area of our region. However, conventional contact tracing did not prove epidemiological linkage among them. These isolates were fully drug-susceptible to the first-line drugs. The comparison of the IS6110RFLP patterns from our isolates against a set of 19 reference Beijing patterns from the RIVM (The Netherlands) confirmed that the strains belonged to the Beijing lineage. These findings might be partially explained by the important migration phenomena occurred during the last decade. Further surveillance studies would help in the following of Beijing family strain dissemination in our community. Durante un estudio poblacional para genotipificar aislamientos de Mycobacterium tuberculosis de Gran Buenos Aires Norte, se encontraron aislamientos con patrones moleculares relacionados con el genotipo Beijing. Cinco de 590 (0,85%) pacientes tuvieron aislamientos con un patrón de spoligotyping idéntico al de la familia Beijing. Dos de esos aislamientos mostraron un patrón de IS6110 RFLP idéntico, por lo que finalmente fueron encontrados cuatro patrones diferentes conteniendo entre 11 y 19 bandas. Las cepas fueron aisladas de personas jóvenes incluyendo un niño de siete años de edad, todos ellos nacidos en Argentina y residentes en un pequeño distrito de nuestra región. Sin embargo, no pudo hallarse ninguna conexión epidemiológica entre ellos. La comparación de los patrones de IS6110 RFLP de los aislamientos con un panel de 19 cepas Beijing de referencia del RIVM (Holanda), confirmó que estas cepas pertenecían a ese linaje. Estos hallazgos podrían explicarse, parcialmente, por el importante fenómeno migratorio ocurrido la pasada década. Futuros estudios de vigilancia epidemiológica podrían contribuir en el seguimiento de la diseminación de las cepas de la familia Beijing de M. tuberculosis en nuestra comunidad.